Analisis Pengaruh Motivasi, Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan Di Yogya Mall Brebes - Tri Herawati; Gian Fitralisma; Indah Dewi Mulyani; Muhammad Syaifulloh (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of motivation, organizational culture, and work environment on employee performance at Yogya Mall Brebes. Methods of collecting data by observing, interviewing and distributing questionnaires to respondents of employees of Yogya Mall Brebes through offline using a questionnaire. The population of Yogya Mall's fashion division employees is 40 employees. The data analysis method is using multiple regression analysis using spss 22. The results of the multiple regression test show that the partial t test of the motivation variable has a positive effect on employee performance with a tcount value of 2.680 > from 1.68830 with a significant level of 0.02 the level is smaller of 0.05, the Organizational Culture variable has a positive effect on employee performance with a tcount value of 1.943 > from 1.68830 with a significant level of 0.00 the level is smaller than 0.05, the Organizational Culture variable has a positive effect on employee performance with a tcount value of 1.690 > from 1.68830 with a significant level of 0.003 the level is smaller than 0.05, has a positive effect on employee performance at Yogya Mall Brebes. Then simultaneously (F) Fcount of 2.941 > Ftable 2.87 with a probability of 0.01 <0.05, then the hypothesis that all independent variables have a simultaneous effect can be accepted.